Reduced graphene oxide supported molybdenum trioxide nanoribbon composite, preparation method and application thereof in sensing material

CN116297700BActive Publication Date: 2026-10-16GUANGZHOU CIVIL AFFAIRS DEV RES CENT (GUANGZHOU SOCIAL ORG SERVICE EXCHANGE CENT GUANGZHOU COMMUNITY GOVERNANCE SERVICE GUIDANCE CENT) +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310083454.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-14
Publication Date
2026-10-16
Estimated Expiration
2043-01-14

AI Technical Summary

Technical Problem

[0005]目前已有报道的气体传感材料提升气敏性能效果显著的贵金属材料价格昂贵、储量有限,成本高;有的复合材料虽然其气敏性好,但是其循环稳定性和长期稳定性不够理想,导致了使用成本的进一步升高

Benefits of technology

[0030] 1. This invention uses a hydrothermal synthesis method, which is simple, low-cost, and does not pollute the environment. The resulting product has a good crystal form and a high yield, reaching 75-85%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116297700B_ABST
    Figure CN116297700B_ABST
Patent Text Reader

Abstract

The application discloses a reduced graphene oxide loaded molybdenum trioxide nanobelt composite material and application thereof, and is prepared by reacting ammonium heptamolybdate and graphene oxide through a hydrothermal method, and washing and drying a reaction product to obtain the reduced graphene oxide loaded molybdenum trioxide nanobelt composite material; a preparation method thereof comprises the following steps: 1) ammonium heptamolybdate is added into deionized water and stirred to obtain an ammonium heptamolybdate solution, graphene oxide is added and uniformly dispersed, and then nitric acid is added to uniformly stir and adjust the pH value of the solution to 0-1.5; and 2) the mixed solution is placed in an oven, and hydrothermal reaction is carried out at 140-220 DEG C for 4-30 h; after being cooled to room temperature, the reaction product is washed and dried to obtain the reduced graphene oxide loaded molybdenum trioxide nanobelt composite material. The method is simple in process and low in cost, and the composite material has excellent selectivity to ethylenediamine; at room temperature, the response value of the composite material to 100 ppm ethylenediamine is higher than 800, the response time is 5-10 s, and the composite material has high sensitivity and fast response.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal oxide nanomaterials technology, and relates to a gas-sensitive material, specifically a reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material, its preparation method, and its application. Background Technology

[0002] With the increasing severity of air pollution, controlling and improving air quality has attracted worldwide attention. Organic amines, especially volatile organic amines, are released from rotting food, chemical intermediates in chemical processes, and pharmaceutical companies. Ethylenediamine (EDA, C2H8N2) is a hazard to environmental pollution and human health due to its toxicity (causing radiation to the eyes, skin, or upper respiratory tract), volatility, flammability, and explosiveness. Therefore, real-time and effective detection and monitoring of it is essential. However, existing detection methods largely rely on expensive laboratory equipment, such as gas chromatography, high-performance liquid chromatography, colorimetry, and luminescence methods. Therefore, convenient real-time detection of volatile organic compounds (VOCs) remains a key challenge in practical applications. Compared with other gas detection methods, metal oxide semiconductor-based gas sensors are receiving increasing attention due to their significant advantages such as low cost, small size, good production flexibility, compatibility with electronic systems, and ease of operation. Many metal oxides, such as zinc oxide, tin dioxide, iron oxide, titanium dioxide, and chromium oxide, have been widely used in the preparation of volatile organic amine sensors.

[0003] Molybdenum trioxide (MoO) is a broadband semiconductor with a bandwidth of 2.39–2.9 eV, exhibiting three crystalline phases (hexagonal, metastable monoclinic, and stable orthorhombic). In sensing applications, research primarily focuses on the thermodynamically stable orthorhombic phase. The morphology of a material is closely related to its specific surface area and electron transport. One-dimensional MoO nanoribbons possess a high area-to-volume ratio and unique physical and chemical properties. Their one-dimensional axis provides a pathway for rapid signal transmission by reducing the large potential barrier, thus rapidly becoming a research hotspot in gas-sensitive materials. However, MoO remains limited by low conductivity, high operating temperature, and low sensitivity. To improve the gas-sensing performance of MoO, numerous attempts have been made, such as modification with noble metals, doping with other metals, or combining with other sensor materials.

[0004] Reduced graphene oxide possesses a high specific surface area and abundant functional groups, making it widely applicable in the field of composite materials. Its excellent room-temperature high-speed carrier mobility, perfect quantum tunneling effect, half-integer quantum Hall effect, and non-vanishing conductivity, among other electrical properties, make it widely used in gas-sensitive composite materials.

[0005] Currently reported gas sensing materials that significantly improve gas sensing performance are made of precious metals, which are expensive, have limited reserves, and are costly. Some composite materials, although they have good gas sensitivity, do not have ideal cycle stability and long-term stability, which leads to further increases in usage costs. Summary of the Invention

[0006] This invention addresses the aforementioned technical problems in the prior art by utilizing the superior conductivity, large surface area, and chemical stability of reduced graphene oxide to synthesize a low-cost sensing material with high response values, rapid detection, and good stability at room temperature via a hydrothermal method. Based on this, the present invention protects the following technical solution:

[0007] A reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material is obtained by reacting ammonium heptamolybdate and graphene oxide via a hydrothermal method, and then washing and drying the reaction product.

[0008] The above-mentioned method for preparing reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material includes the following steps:

[0009] 1) Add ammonium heptamolybdate to deionized water and stir until homogeneous to obtain ammonium heptamolybdate solution. Add graphene oxide and disperse evenly. Then add nitric acid and stir until homogeneous to adjust the pH of the solution to 0-1.5.

[0010] 2) Place the mixed solution from step 1) in an oven and perform a hydrothermal reaction at 140-220℃ for 4-30 hours. After cooling to room temperature, wash and dry the reaction product to obtain the reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material.

[0011] 3. The preparation method according to claim 2, characterized in that: in step 1), the mass ratio of the raw material ammonium heptamolybdate to graphene oxide is (0.50-0.70):(0.001-0.01), preferably (0.50-0.7):(0.001-0.007) or (0.50-0.7):(0.001-0.005) or (0.58-0.64):(0.001-0.007) or (0.60-0.64):(0.001-0.005) or (0.60-0.64):(0.003-0.005) or (0.61-0.63):0.005;

[0012] The mass ratio of ammonium heptamolybdate to deionized water is (0.50-0.70):(15-50), preferably (0.50-0.70):(15-40), (0.50-0.70):(15-30), (0.55-0.65):(15-40), or (0.58-0.64):(20-30).

[0013] Preferably, the nitric acid is concentrated nitric acid.

[0014] In step 1), ammonium heptamolybdate is added to deionized water and magnetically stirred for 10-30 minutes to obtain an ammonium heptamolybdate solution. After adding graphene oxide, the solution is ultrasonically treated at 20-50℃ for 10-30 minutes. After adding nitric acid, the solution is stirred for 20-40 minutes.

[0015] In step 2),

[0016] The hydrothermal reaction temperature is 150-210℃, 160-200℃, 170-190℃, or 180℃.

[0017] The hydrothermal reaction time is 12-30h, 16-24h, 18-22h, 19-21h, or 20h.

[0018] After the hydrothermal reaction is completed, the oven is cooled to room temperature, and the product is washed with deionized water and ethanol. It is then dried under vacuum at 50-100℃ for 10-24 hours.

[0019] Preferably, the product is washed 1-5 times with deionized water and ethanol, respectively.

[0020] Application of the reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material prepared by any of the above preparation methods in the detection of ethylenediamine.

[0021] In the application technology solution, the concentration of ethylenediamine is 0.5-150 ppm, preferably 0.5-130 ppm, 0.5-120 ppm, or 0.5-100 ppm.

[0022] Application of the reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material prepared by any of the above methods in the preparation of sensing materials for detecting ethylenediamine.

[0023] The principle of this invention is:

[0024] Specific surface area and morphology significantly influence gas sensing performance. Increasing the specific surface area of ​​materials, utilizing the size effect of nanomaterials, gives one-dimensional nanomaterials a greater advantage in gas sensing applications. The large specific surface area of ​​one-dimensional nanomaterials increases the contact between the material and reactants, facilitating the adsorption and desorption of more target gas molecules. Electrons can transport along the axis of one-dimensional nanomaterials, significantly improving the electron diffusion rate within the material. The numerous active sites on the surface of one-dimensional nanomaterials enhance their gas sensing performance; however, the large number of homojunctions between MoO3 nanoparticles leads to severe electron scattering, resulting in high sensor resistance. By adding graphene oxide, the synthesized product consists of numerous nanoribbons with an average length of approximately 5-15 μm, which are loaded onto graphene nanosheets. During the preparation of one-dimensional α-MoO3 nanoribbons, the one-dimensional structure is obtained by controlling the appropriate pH value. The one-dimensional molybdenum trioxide nanoparticles prepared under hydrothermal conditions are mainly due to the preferred orientation growth of orthorhombic molybdenum trioxide. This is because the basic structural unit of orthorhombic molybdenum trioxide, the [MoO6] octahedron, is connected at the same angle along the

[100] direction and at the same edge along the

[001] direction. Meanwhile, H... + It can adsorb onto the

[010] crystal plane, inhibiting its growth rate and changing the crystal plane growth rate ratio. Since the [MoO6] octahedrons arranged along

[001] will form more Mo-O-Mo bonds, releasing more energy and making the structure more stable, MoO3 tends to preferentially grow along the c-axis. H + The amount added directly determines the morphology of the sample, H + Insufficient addition may result in rod-shaped product samples with a small aspect ratio, uneven morphology, and large grain size. Adding excessive H... + A smooth sample surface reduces the number of active sites in contact with the target gas, which is detrimental to the material's gas-sensing properties. Appropriate amounts of H2O... +It can generate fibrous or ribbon-like MoO3. Adding nitric acid to an ammonium molybdate solution to control the pH value modulates the morphology of molybdenum trioxide, allowing the ammonium molybdate to generate one-dimensional molybdenum trioxide nanorods with diameters of approximately 100-300 nm and lengths of approximately 5-30 μm under hydrothermal conditions. Graphene oxide forms reduced graphene oxide after hydrothermal treatment, exhibiting better stability and higher conductivity. Besides the homojunctions between the MoO3 nanorods, numerous MoO3 / graphene contacts are generated in the sensing layer after composite with graphene. Due to the different work functions of MoO3 and reduced graphene oxide, a Schottky barrier is formed. Therefore, electron diffusion is easier in the MoO3 nanoribbon / graphene composite material than in pure MoO3 nanorods. Furthermore, the one-dimensional nanoribbons and two-dimensional graphene form a three-dimensional network structure, increasing the specific surface area of ​​the material. When the sensor is in the air, oxygen molecules adsorb onto the MoO3 nanorods and spontaneously diffuse to the homojunctions due to the concentration gradient. The adsorbed oxygen can capture electrons in the conduction band of MoO3, forming chemisorbed oxygen ions (mainly O2). - (As can be seen from formulas 1 and 2). Therefore, an electron depletion layer forms on both the surface and interface regions of MoO3, resulting in a high potential barrier at the homojunction. Consequently, when equilibrium is reached, the resistance of the sensing layer remains at a relatively high level.

[0025]

[0026] O2(ad)+e - →O2 - (ad) (2)

[0027] C2H8N2+4O2 - (ad)→2CO2+4H2O+2N2+e- (3)

[0028] When the sensing layer is exposed to the target gas, ethylenediamine (C2H8N2) can react with O2 on the surface of the nanoribbons. - A reaction occurs, disrupting the equilibrium. O2 in the interface region... - It diffuses back towards the surface and reacts with excess C2H8N2 until a new equilibrium is formed. (The text then abruptly shifts to a discussion of C2H8N2 and O2.) -During the reaction, trapped electrons are released, causing the electron depletion layer to narrow. Therefore, the barrier height at the homojunction decreases to a relatively low level, leading to an increase in the conductivity of the sensing layer. The higher surface area and the provision of numerous active sites facilitate the absorption / diffusion of gas molecules, which improves the reaction between C2H8N2 and chemisorbed oxygen during sensing. Defects or edge regions in the graphene nanosheets also influence the carrier density of the MoO3 nanoribbon / rGO sensing layer. Therefore, the sensitivity of the MoO3 nanoribbon / rGO sensor is higher than that of a pure MoO3 sensor. This phenomenon is more pronounced at higher ethylenediamine concentrations, as more ethylenediamine gas diffuses into the sensing layer and reacts with chemisorbed oxygen ions on the surface.

[0029] The beneficial effects of this invention are:

[0030] 1. This invention uses a hydrothermal synthesis method, which is simple, low-cost, and does not pollute the environment. The resulting product has a good crystal form and a high yield, reaching 75-85%.

[0031] 2. The composite material of the present invention has excellent selectivity for ethylenediamine, with a response value of over 800 for 100 ppm ethylenediamine at room temperature and a response time of 5-10 s, exhibiting high sensitivity and fast response.

[0032] 3. The composite material of the present invention has excellent gas-sensing properties. It has been verified that it has excellent long-term stability and cycle stability, and has broad application prospects in the field of detecting volatile organic compounds. Attached Figure Description

[0033] Figure 1 The XRD spectra of the reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material and the control molybdenum trioxide nanoribbon of the present invention are shown below.

[0034] Figure 2 This is a scanning SEM image of the reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material of the present invention;

[0035] Figure 3 The dynamic response diagrams of the reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material and the control molybdenum trioxide nanoribbon to different concentrations of ethylenediamine are shown.

[0036] Figure 4 The figure shows the results of five cycles of stability testing of the reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material and the control molybdenum trioxide nanoribbon against 100 ppm ethylenediamine.

[0037] Figure 5 The graph shows the selectivity test results of the reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material and the control molybdenum trioxide nanoribbon for ethylenediamine.

[0038] Figure 6 The figure shows the long-term stability test results of the reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material and the control molybdenum trioxide nanoribbon to ethylenediamine.

[0039] Explanation of reference numerals in the figures: MoO3 indicates the molybdenum trioxide nanoribbons prepared by the method in Example 1, and MoO3 / rGO-5 indicates the reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material of the present invention. The raw material ratio during preparation is 0.618g ammonium heptamolybdate plus 0.005g graphene. Detailed Implementation

[0040] The present invention will be further described below with reference to embodiments, but these embodiments are not intended to limit the scope of the invention.

[0041] Unless otherwise specified, the experimental methods in the following examples are conventional methods; the chemical reagents and materials used are conventional reagents and materials in the art and can be obtained commercially.

[0042] Example 1: Preparation of molybdenum trioxide nanoribbons

[0043] Follow these steps:

[0044] 1) Weigh 0.618g of ammonium heptamolybdate ((NH4)6Mo7O 24 Add the solution to 25 mL of deionized water and stir magnetically for 10 min to obtain a clear ammonium heptamolybdate solution. Then, measure 2.5 mL of concentrated nitric acid (12 mol / L) and slowly add it dropwise to the ammonium heptamolybdate solution while stirring continuously for 30 min.

[0045] 2) The mixed solution obtained in step 1) was placed into a 50 mL reaction vessel with a polytetrafluoroethylene liner and placed in an oven at 180℃ (i.e., hydrothermal temperature) for 20 h (i.e., hydrothermal time). After the reaction was completed, the oven was cooled to room temperature at a rate of 5℃ / min. The product was washed three times by centrifugation with deionized water and then three times by centrifugation with ethanol. It was then dried in an oven at 80℃ under vacuum for 12 h to obtain molybdenum trioxide nanoribbons (MoO3 nanoribbons).

[0046] This embodiment also tested the gas-sensing properties of MoO3 nanoribbons prepared with different hydrothermal times and temperatures for ethylenediamine.

[0047] Comparison of different hydrothermal temperatures: Using the above method, the MoO3 nanoribbons were hydrothermally heated at 100, 140, 180, and 220℃ for 12 hours. The results showed that the response values ​​of the MoO3 nanoribbons prepared at 100, 140, 180, and 220℃ to 100 ppm ethylenediamine at room temperature were 39.7, 122.6, 297.4, and 203.5, respectively. This indicates that the MoO3 nanoribbons prepared at 180℃ had the highest response value to 100 ppm ethylenediamine.

[0048] Comparison of different hydrothermal times: Using the above method, the MoO3 nanoribbons were hydrothermally heated at 180℃ for 4, 12, 20, and 30 hours respectively. The results showed that the response values ​​of the MoO3 nanoribbons prepared by hydrothermal heating for 4, 12, 20, and 30 hours to 100 ppm ethylenediamine at room temperature were 212.1, 297.4, 435.3, and 386.1, respectively. This indicates that the MoO3 nanoribbons prepared by hydrothermal heating for 20 hours at 180℃ had the highest response value to 100 ppm ethylenediamine.

[0049] Example 2: Preparation and performance testing of the reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material of the present invention.

[0050] I. Preparation Method

[0051] Follow these steps:

[0052] 1) Graphene oxide (GO) was prepared according to the Hummers method.

[0053] 2) Weigh out 0.618g of ammonium heptamolybdate ((NH4)6Mo7O 24 Add the solution to 25 mL of deionized water and stir magnetically for 10 min to obtain a clear ammonium heptamolybdate solution. Then add 0.005 g of graphene oxide (GO) and sonicate at 20-40 °C for 20 min to obtain a homogeneous solution. Measure 2.5 mL of concentrated nitric acid (12 mol / L) and slowly add it dropwise to the above mixed solution and continue stirring for 30 min.

[0054] 3) The mixed solution obtained in step 2) was placed into a 50 mL reaction vessel with a polytetrafluoroethylene liner and placed in an oven at 180 °C for 20 h. After the reaction was completed, the oven was cooled to room temperature at a rate of 5 °C / min. The product was washed three times by centrifugation with deionized water and then three times by centrifugation with ethanol. It was then dried in an oven at 80 °C under vacuum for 12 h to obtain a reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material (denoted as MoO3 / rGO-5).

[0055] The XRD patterns of the material reveal the crystal structure and diffraction planes of the synthesized material, such as... Figure 1As shown, the XRD pattern of the control MoO3 nanoribbons prepared in Example 1 shows peak positions of 23.2°, 25.8°, 27.3°, 33.3°, 39.01°, 55.1°, 56.5°, and 58.9°. [1 1 0], [0 4 0], [0 2 1], [1 1 1], [0 6 0], [1 1 2], [0 4 2], and [0 8 1] represent the diffraction planes. All diffraction peaks in the XRD pattern are indexed to the orthorhombic phase MoO3 with JCPDS card number (35-0609). Furthermore, the diffraction peaks at 2θ values ​​of 25.8° and 39.01° on the [0 4 0] and [0 6 0] diffraction planes demonstrate the layered crystal structure of the α-MoO3 nanowires. No graphene diffraction peaks were observed in the XRD pattern of MoO3 / rGO-5, which was analyzed to be due to the low rGO content.

[0056] SEM images of MoO3 / rGO-5 are shown below. Figure 2 As shown, the synthesized product consists of a large number of nanoribbons with a length of about 5-15 μm, which are loaded onto graphene nanosheets.

[0057] II. Gas Sensing Performance Test for Ethylenediamine

[0058] Test method:

[0059] The target gas, volatile liquid ethylenediamine, is heated and diffused within an 18L sealed chamber to create a test atmosphere of a specific concentration. The gas sensitivity test is conducted entirely at room temperature. The gas sensor performance testing instrument consists of an electrical signal generation system, a testing system, an information collection system, and an information processor. The testing system is a gas sensitivity tester (model: WS-30B, made in Zhengzhou, China).

[0060] Preparation before testing: Prepare the gas-sensitive element. Take 1 mg of the previously prepared MoO3 / rGO-5 composite material in a mortar, add 1 mL of anhydrous ethanol, mix into a paste, and use a brush to evenly and thinly apply the paste to the surface of the interdigital electrode (size: 10×8×0.15 mm). Transfer to an 80℃ forced-air oven to dry for 6 hours to ensure complete evaporation of ethanol.

[0061] Gas Sensitive Tester Operating Procedures: Insert the gas-sensitive element into the test circuit board, and adjust the test baseline to a suitable position by adjusting the load resistor. After the baseline stabilizes, begin the formal test. For the first 300 seconds, measure the air resistance R of the gas-sensitive element in clean air. a Turn on the built-in fan inside the chamber, and inject a certain amount of target gas into the test chamber after 300 seconds, then quickly seal it. The resistance reading at this time is the resistance value R of the gas-sensitive element in the target gas. gThe gas concentration and the volume of the volatile liquid are calculated using formula (4). After the data acquisition is completed, the sealed cavity is opened, the target gas in the cavity is drained, the target gas concentration is changed, and the above steps are repeated.

[0062] The formulas for calculating gaseous concentration and corresponding liquid volume are derived from the ideal gas law PV = nRT:

[0063] V 气 =(P 瓶 *C ppm *V 瓶 *M 气 ) / (22.4*ρ 气 *ω 气 (4)

[0064] In formula (4), M 气 V 气 ρ 气 ω 气 , , and , respectively, represent the molar mass, volume, density, and mass fraction of the liquid corresponding to the target gas; P 瓶 and V 瓶 and are the pressure and volume of the space containing the gas, respectively; that is, C ppm The desired gas concentration is given. The material's sensitivity (response value) is defined as: R = R0 g / R a R represents the response value.

[0065] 1. Dynamic response test

[0066] The results are as follows Figure 3 As shown, experimental results indicate that the response value increases with increasing ethylenediamine gas concentration. At room temperature (25℃), the response values ​​of MoO3 (the control prepared in Example 1) to ethylenediamine at concentrations of 0.5, 0.7, 1, 3, 5, 7, 10, 30, 50, 70, and 100 ppm are 1.0, 1.1.1, 1.3, 1.6, 3.9, 10.7, 99.7, 219.8, and 435.3, respectively. The response values ​​of the composite material MoO3 / rGO-5 of this invention to ethylenediamine at concentrations of 0.5, 0.7, 1, 3, 5, 7, 10, 30, 50, 70, and 100 ppm are 1.1, 1.5, 1.8, 4.4, 6.3, 7.4, 11, 10.6, 56.3, 221.4, 412.3, and 834.7, respectively.

[0067] 2. Cyclic stability test

[0068] Test Method: Insert the gas-sensitive element into the test circuit board and adjust the test baseline to a suitable position by adjusting the load resistor. After the baseline stabilizes, begin the formal test. Turn on the built-in fan inside the chamber and measure the air resistance R of the gas-sensitive element in clean air for the first 300 seconds. a After 300 seconds, 100 ppm ethylenediamine gas is injected into the test chamber, and the chamber is quickly sealed. The resistance reading at this point is the resistance value R of the gas-sensitive element in the target gas. g After data acquisition is complete, open the sealed cavity, purge the target gas from the cavity, and repeat the above steps four times to measure the material's cyclic stability.

[0069] The results of five cycles of testing with 100ppm ethylenediamine gas at 25℃ are as follows: Figure 4 As shown, the results indicate that the response value fluctuations of both the control MoO3 and the composite material MoO3 / rGO-5 of the present invention are less than 5% of the mean, indicating that both materials have good stability.

[0070] 3. Gas selectivity test

[0071] Following the previous method for testing the gas-sensing properties of ethylenediamine, gas selectivity tests were performed on the prepared pure MoO3, MoO3 / rGO-5, and composite materials by introducing 100 ppm of triethylamine, ammonia, ethanol, formaldehyde, acetone, and ethylenediamine, respectively.

[0072] The results are as follows Figure 5 As shown, experimental results indicate that the pure MoO3 and the MoO3 / rGO-5 composite material of the present invention exhibit excellent selectivity for ethylenediamine in the presence of 100 ppm interfering gases (triethylamine, ammonia, ethanol, formaldehyde, acetone, and hydrogen).

[0073] 4. Long-term stability test

[0074] Following the previous method for testing the gas sensitivity of ethylenediamine, the long-term stability of the prepared MoO3 / rGO-5 composite material was tested, and the gas sensitivity of ethylenediamine was tested weekly for eight consecutive weeks.

[0075] The results are as follows Figure 6 As shown, the results indicate that after eight consecutive weeks of testing, the response value of the MoO3 / rGO-5 composite material decays very little, with the fluctuation range of the maximum and minimum values ​​within 5%, indicating that the composite material of the present invention has good long-term stability.

[0076] Example 3: Experiments with different ratios of ammonium molybdate and graphene

[0077] MoO3 / rGO composite materials were prepared according to the method described in Example 2. 0.618 g of ammonium heptamolybdate was weighed, and different masses of graphene oxide were added at different amounts: 0.001, 0.003, 0.005, 0.007, 0.01, and 0.015 g. The gas-sensitivity properties of the prepared samples to ethylenediamine were tested (using the same method as in Example 2). The results are as follows:

[0078] Sample 1: The mass ratio of ammonium heptamolybdate to graphene oxide was 0.62:0.001. The prepared MoO3 / rGO-1 had a response value of 483.6 to 100 ppm ethylenediamine.

[0079] Sample 2: The mass ratio of ammonium heptamolybdate to graphene oxide was 0.62:0.003, and the response value of the prepared MoO3 / rGO-3 to 100 ppm ethylenediamine was 654.8.

[0080] Sample 3: The mass ratio of ammonium heptamolybdate to graphene oxide was 0.62:0.005 (i.e. the sample prepared in Example 2), and the response value of the prepared MoO3 / rGO-7 to 100 ppm ethylenediamine was 834.7.

[0081] Sample 4: The mass ratio of ammonium heptamolybdate to graphene oxide was 0.62:0.007, and the response value of the prepared MoO3 / rGO-7 to 100 ppm ethylenediamine was 302.1.

[0082] Sample 5: The mass ratio of ammonium heptamolybdate to graphene oxide was 0.62:0.01, and the prepared MoO3 / rGO-10 had a response value of 161.7 to 100 ppm ethylenediamine.

[0083] Sample 6: The mass ratio of ammonium heptamolybdate to graphene oxide was 0.62:0.015, and the prepared MoO3 / rGO-15 had a response value of 80.2 to 100 ppm ethylenediamine.

[0084] The results above show that when the mass ratio of ammonium heptamolybdate to graphene oxide is 0.62:0.005, the prepared MoO3 / rGO-5 exhibits the highest response value to 100 ppm ethylenediamine.

Claims

1. The application of a reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material in the detection of ethylenediamine or in the preparation of a sensing material for detecting ethylenediamine, wherein the reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material is obtained by reacting ammonium heptamolybdate and graphene oxide via a hydrothermal method, and the reaction product is washed and dried.

2. The application according to claim 1, characterized in that: The preparation method of the reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material includes the following steps: 1) Add ammonium heptamolybdate to deionized water and stir until homogeneous to obtain ammonium heptamolybdate solution. Add graphene oxide and disperse evenly. Then add nitric acid and stir until homogeneous to adjust the pH of the solution to 0-1.

5. 2) Place the mixed solution from step 1) in an oven and perform a hydrothermal reaction at 140-220 ℃ for 4-30 h. After cooling to room temperature, wash and dry the reaction product to obtain the reduced graphene oxide-supported molybdenum trioxide nanoribbon composite material.

3. The application according to claim 2, characterized in that: In step 1), the mass ratio of the raw material ammonium heptamolybdate to graphene oxide is (0.50-0.70): (0.001-0.01); The mass ratio of ammonium heptamolybdate to deionized water is (0.50-0.70): (15-50).

4. The application according to claim 2, characterized in that: The nitric acid mentioned is concentrated nitric acid.

5. The application according to claim 2, characterized in that: In step 1), ammonium heptamolybdate is added to deionized water and magnetically stirred for 10-30 min to obtain an ammonium heptamolybdate solution. After adding graphene oxide, the solution is ultrasonically treated at 20-50 ℃ for 10-30 min, and then nitric acid is added and stirred for 20-40 min.

6. The application according to claim 2, characterized in that: In step 2), The hydrothermal reaction temperature is 150-210 ℃. The hydrothermal reaction time is 12-30 h; After the hydrothermal reaction is completed, the oven is cooled to room temperature, and the product is washed with deionized water and ethanol. It is then dried under vacuum at 50-100 °C for 10-24 h.

7. The application according to claim 6, characterized in that: Wash with deionized water and ethanol 1-5 times respectively.

8. The application according to claim 1, characterized in that: The concentration of the ethylenediamine is 0.5-150 ppm.

Citation Information

Patent Citations

  • All-solid-state potassium ion selective electrode based on graphene-molybdenum trioxide and preparation method and application thereof

    CN113155933A